Leadership, climate, and satisfaction: A behavioural approach to teacher retention - Dhamayanti, Yoana Francisca Novia; Putranta, Martinus Parnawa (Indonesia Research and Study Center, 2026)
From an organizational behavior perspective, teacher retention reflects the interplay of leadership practices, organizational climate, and work-related evaluative mechanisms. This study examines how school climate and principals’ decision-making style influence teacher performance, job satisfaction, and teachers’ intention to stay in faith-based schools. Using a quantitative explanatory design, data were collected from 200 junior and senior high school teachers across 16 faith-based schools in Java, Indonesia, and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that both school climate (β = 0.333, p < 0.01) and principals’ decision-making style (β = 0.402, p < 0.001) are positively associated with teacher performance. Teacher performance significantly predicts job satisfaction (β = 0.655, p < 0.001), which in turn has a positive effect on intention to stay (β = 0.511, p < 0.001). Further analysis confirms that job satisfaction partially mediates the relationship between teacher performance and intention to stay. These findings contribute to organizational behavior and educational leadership literature by illustrating how leadership and climate function as organizational resources supporting teacher retention. Practically, the study highlights the importance of participative decision-making and supportive school climates in sustaining a committed teaching workforce.